Arrays of low‐temperature plasma probes for ambient ionization mass spectrometry. (12th December 2012) - Dalgleish, Jon K.; Wleklinski, Michael; Shelley, Jacob T.; Mulligan, Christopher C.; Ouyang, Zheng; Graham Cooks, R.
<x xml:space="preserve">Abstract</x> RATIONALE This paper reports the development of arrays of capillary‐based low‐temperature plasma (LTP) probes for direct sample analysis. These probe arrays allow a higher surface area to be analyzed, increasing the throughput in large sample analysis. Validation of these arrays was performed on illicit, cathinone‐based drugs marketed as 'bath salts'. METHODS LTP arrays consisting of 1, 7, and 19 probes were constructed with quartz capillaries and held together with silver epoxy resin adhesive. Three drugs, mephedrone, methylone and methylenedioxypyrovalerone, were analyzed with each plasma ion source and an ion trap mass spectrometer in full MS and in MS/MS positive ion mode. Chemical and thermal footprints were determined for each source. A reactive probe design was used to inject trifluoroacetic anhydride directly into the plasma stream for on‐line derivatization. RESULTS Small LTP probes and bundled arrays provide low picogram level limits of detection for mephedrone, methylone and methylenedioxypyrovalerone. Bundling the probes together in larger arrays increases the surface area analyzed by a factor of ten, while maintaining surface temperatures below 40 °C. Selectivity towards mephedrone and methylone was increased using trifluoracetylation under ambient ionization conditions. CONCLUSIONS Low‐temperature plasma ionization sources allow rapid detection of illicit 'bath salt' drugs in low amounts. The sources have a larger sampling area that allows faster detection of each analyte, and selectivity towards the selected drug is enhanced by adding reagents directly into the plasma stream. Copyright © 2012 John Wiley & Sons, Ltd.